1998
DOI: 10.1074/jbc.273.9.5081
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stressing of Integrin Receptors Induces Enhanced Tyrosine Phosphorylation of Cytoskeletally Anchored Proteins

Abstract: Physical forces play a fundamental role in the regulation of cell function in many tissues, but little is known about how cells are able to sense mechanical loads and realize signal transduction. Adhesion receptors like integrins are candidates for mechanotransducers. We used a magnetic drag force device to apply forces on integrin receptors in an osteoblastic cell line and studied the effect on tyrosine phosphorylation as a biochemical event in signal transduction. Mechanical stressing of both the ␤1 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 41 publications
5
149
0
Order By: Relevance
“…In addition, retrograde flux of FAK may have a profound effect on the state of phosphorylation at focal adhesions and actin filaments, which in turn affects the maturation and turnover of focal adhesions (Webb et al, 2004). Our results further suggest that the flux of focal adhesion proteins requires tyrosine phosphorylation, which, in conjunction with the small GTPases Rac and Rho, represents the primary molecular switches in response to integrin-ECM anchorage and mechanical signals (Burridge et al, 1992;Schmidt et al, 1998). Tyrosine phosphorylation regulates the dynamic turnover of focal adhesion proteins through a number of substrates including paxillin, p130Cas, and FAK (Carragher and Frame, 2004).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In addition, retrograde flux of FAK may have a profound effect on the state of phosphorylation at focal adhesions and actin filaments, which in turn affects the maturation and turnover of focal adhesions (Webb et al, 2004). Our results further suggest that the flux of focal adhesion proteins requires tyrosine phosphorylation, which, in conjunction with the small GTPases Rac and Rho, represents the primary molecular switches in response to integrin-ECM anchorage and mechanical signals (Burridge et al, 1992;Schmidt et al, 1998). Tyrosine phosphorylation regulates the dynamic turnover of focal adhesion proteins through a number of substrates including paxillin, p130Cas, and FAK (Carragher and Frame, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Given the response of tyrosine phosphorylation to mechanical signals (Pelham and Wang, 1997;Schmidt et al, 1998), we asked whether tyrosine phosphorylation might be involved in regulating focal adhesion fluxes. Immunofluorescence localization showed that phosphotyrosine was concentrated only at focal adhesions irrespective of the presence of zyxin tails ( Figure 8A).…”
Section: Dependence Of Focal Adhesion Fluxes On Tyrosine Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…RPTP-α can activate Src family kinases (SFKs) within about 300 ms after application of a force on fibronectin beads [65][66][67]. Phosphorylation of mitogen-activated protein kinase (MAPK) has also been reported to increase in response to mechanical stress, suggesting that integrins sense forces regulating gene expression by activation of the MAPK pathway [68], which is known to be downstream of TGF-β signaling [69].…”
Section: Integrins Mediate Interactions Between the Cell And The Extrmentioning
confidence: 99%